2022
DOI: 10.1002/bies.202200181
|View full text |Cite
|
Sign up to set email alerts
|

Importin α/β and the tug of war to keep TDP‐43 in solution: quo vadis?

Abstract: The transactivation response‐DNA binding protein of 43 kDa (TDP‐43) is an aggregation‐prone nucleic acid‐binding protein linked to the etiology of Amyotrophic Lateral Sclerosis (ALS) and Frontotemporal Lobar Degeneration (FTLD). These conditions feature the accumulation of insoluble TDP‐43 aggregates in the neuronal cytoplasm that lead to cell death. The dynamics between cytoplasmic and nuclear TDP‐43 are altered in the disease state where TDP‐43 mislocalizes to the cytoplasm, disrupting Nuclear Pore Complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 75 publications
(134 reference statements)
2
8
0
Order By: Relevance
“…9a-c,f-h). While we and others speculated that FG-Nups might associate with the FG-like repeats that are present in the TDP-43 PrLD [71], here we show that TDP-CTF variants where phenylalanine residues in the PrLD were replaced with glycine, alanine, or tyrosine residues still co-aggregate with Nup62 (Supplementary Fig. 9a).…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…9a-c,f-h). While we and others speculated that FG-Nups might associate with the FG-like repeats that are present in the TDP-43 PrLD [71], here we show that TDP-CTF variants where phenylalanine residues in the PrLD were replaced with glycine, alanine, or tyrosine residues still co-aggregate with Nup62 (Supplementary Fig. 9a).…”
Section: Discussionsupporting
confidence: 39%
“…1). While a recent study reported that binding of the importin-α/KPNB1 complex to the NLS prevents TDP-43 dimerization as the foundation of disaggregation, this in vitro structural analysis was limited to a recombinant soluble fragment of TDP-43 spanning residues aa1-177 that lacked the C-terminal PrLD, which was identified in the present study as the key domain for KPNB1-mediated disaggregation in the context of living cells [71,72]. The existence of a potential additional NLS-independent mechanism to suppress phase transition of RBPs is also supported by the observation that under certain conditions TNPO1 can dissolve truncated FUS lacking the PY-NLS [19,73] and that other NIRs, including KPNB1, can bind the RGG motifs of FUS and reduce its fibrillization [74].…”
Section: Discussionmentioning
confidence: 98%
“…By contrast, importin-α/β1 complex was ineffective against fibrils formed by TDP-43 variants lacking the classical NLS and failed to prevent and reverse the self-assembly of proteins containing a PY-NLS [ 40 ]. The interaction of importin-α/β1 with TDP-43 sterically interferes with NTD-mediated TDP-43 oligomerization, which may contribute to the observed inhibition of TDP-43 self-assembly in presence of the importin-α/β1 heterodimer [ 13 , 38 ]. Similar to FUS, introducing an acetylation mimic in the NLS (K84Q) increases TDP-43 cytoplasmic mislocalization, presumably by disrupting interactions with importin-α-associated KPNB1.…”
Section: Therapeutic Potential Of Nirs Countering Aberrant Phase Tran...mentioning
confidence: 99%
“…One hypothesis is that key proteins of the nuclear pore complex, Importin-α and Importin-β, bind the TDP-43 nuclear-localization-signal and prevent most of its cytoplasmic localization [ 39 ]. Interestingly, recent discoveries indicate that phosphorylation of TDP-43 in proximity to its nuclear-localization-signal prevents binding of Importins [ 39 ] and therefore can promote the cytoplasmic accumulation of the protein, thus suggesting that TDP-43 phosphorylation might be a key process that facilitates redistribution of the protein from the nucleus to the cytoplasm [ 40 ]. Additionally, a recent article by Khalil et al, indicates a new NLS-independent mechanism for TDP-43 cytoplasmic mislocalization, where the activity of karyopherin-β1 (KPNB1/Importin-β), increase the solubility of TDP-43 upon their recruitment to nucleoporin rich pTDP-43 condensates.…”
Section: Part 1 – Tdp-43 Phosphorylation and Its Toxic Role In Axons ...mentioning
confidence: 99%
“…Alternatively, a recent report by Patel et al, has identified that the mRNAs of several RNA-binding proteins, such as Khsrp, are localized to peripheral nerve axons and are locally translated in response to injury [ 57 ]. TDP-43 is known to localize into axons and to carry mRNAs, including its own [ 39 , 40 , 53 ]. Additionally, detailed analysis of axonal transcriptome data from motor neurons revealed that TDP-43 mRNA is abundant in axons [ 58 ].…”
Section: Part 1 – Tdp-43 Phosphorylation and Its Toxic Role In Axons ...mentioning
confidence: 99%